Soft functional interfaces - Steitz, Roland; Dahint, Reiner (Advanced engineering materials, 2011)
This paper summarizes novel aspects of soft functional interfaces as revealed by surface sensitive neutron and X-ray scattering in combination with complementary methods of characterization such as infrared and X-ray photoelectron spectroscopy. The paper exclusively examines stratified soft solid-liquid interfaces and potential precursors. At first the occurrence of depletion layers at the interfaces and their relevance for biocompatibility is discussed. Further, strategies of implementing functional units into surface coatings to achieve interfaces that are reversibly altered as a function of external stimuli are described. The paper finishes with a compilation of protein resistant interfaces and a brief survey on potential repulsion mechanisms.
Gesehen am 21.10.2022